STATE INVESTMENT POLICY IN UKRAINE DURING THE WAR AND POST-WAR PERIOD - TANASIENKO, Nataliia; VRUBLEVSKYI, Ivan; PYATNYCHKA, Vasyl; URIZCHENKO, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The main difficulty of investment processes at the present stage lies in the very limited possibilities for internal accumulations and the inability of domestic investors to fully compensate for the lack of capital investments in wartime conditions. Therefore, the purpose of the article is to characterize the key vectors of the state investment policy in the conditions of war and post-war recovery, which are aimed at creating favorable conditions for investment. Even before the start of the full-scale war, attracting investment to Ukraine was complicated by problems with the investment climate. The two years of hostilities have caused significant turbulence and increased uncertainty in financial markets, which has affected the level of risk and has been reflected in investor behavior. The state should become the main regulator and direct efforts to create favorable conditions for investment. The study analyzed the dynamics of foreign direct investment in and from Ukraine during the pre-war period and during the war, noted the factors that positively and negatively affect the investment climate in the country. The key vectors of the state investment policy in the conditions of the war and the post-war period are considered. In order to quickly restore the country and ensure economic development in the post-war period, it is necessary to conduct a balanced fiscal and budgetary policy, increase the efficiency of expenditures and tax and customs regulation, improve the structure of taxes and benefits, and prevent abuses by state authorities in relation to business